Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran SKI Melalui Implementasi Metode Pembelajaran Berbasis Proyek : (Studi Kasus di Kelas XI IPA Madrasah Aliyah 1 Kampar) - Rodiah Rodiah; Romadlon Khusnul Kiro; Riskiyah Riskiyah (Jurnal Pendidikan Dirgantara, 2024)
Learning Islamic Cultural History (SKI) at Madrasah Aliyah presents unique challenges, particularly in increasing students' interest and learning outcomes. Conventional methods such as lectures and memorization often result in low student engagement, leading to suboptimal understanding and poor learning outcomes. To address this issue, this study implements project-based learning (PjBL) as an alternative approach to enhance student learning outcomes. This study examines the effectiveness of project-based learning in improving student achievement in SKI subjects at Madrasah Aliyah 1 Kampar, specifically in class XI Science. Using the Kemmis and McTaggart classroom action research (CAR) model, the research was conducted in two cycles, involving planning, implementation, observation, and reflection stages. Data were collected through learning outcome tests, observation sheets, interviews, and student and teacher questionnaires. Both quantitative and qualitative analyses were performed to comprehensively assess the effectiveness of this method. The findings indicate that implementing project-based learning positively impacts student learning outcomes. The average student score increased significantly from the first to the second cycle. Moreover, student engagement in learning activities improved, as seen in their active participation in discussions, material exploration, and teamwork on assigned projects. Additionally, this method helped students develop critical thinking, problem-solving, and collaboration skills essential in modern education. The study confirms that project-based learning is an effective strategy for enhancing SKI education in Madrasah Aliyah. These findings suggest that educators should adopt more innovative and interactive teaching methods to foster student engagement and deeper understanding in learning.